Patient acceptability of wearable vital sign monitoring technologies in the acute care setting: A systematic review - Sprogis, Stephanie K.; Currey, Judy; Considine, Julie (Journal of clinical nursing, 2019)
Aims and objectives To examine patient acceptability of wearable vital sign monitoring devices in the acute setting. Background Wearable vital sign monitoring devices may improve patient safety, yet hospital patients' acceptability of these devices is largely unreported. Design A systematic review. Methods Cumulative Index to Nursing and Allied Health Literature Complete, MEDLINE Complete and EMBASE were searched, supplemented by reference list hand searching. Studies were included if they involved adult hospital patients (≥18 years), a wearable monitoring device capable of assessing ≥1 vital sign, and measured patient acceptability, satisfaction or experience of wearing the device. No date restrictions were enforced. Quality assessments of quantitative and qualitative studies were undertaken using the Downs and Black Checklist for Measuring Study Quality and the Critical Appraisal Skills Programme Qualitative Research Checklist, respectively. Meta‐analyses were not possible given data heterogeneity and low research quality. Reporting adhered to the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses guidelines and a Preferred Reporting Items for Systematic Reviews and Meta‐Analyses checklist was completed. Results Of the 427 studies screened, seven observational studies met the inclusion criteria. Six studies were of low quality and one was of high quality. In two studies, patient satisfaction was investigated. In the remaining studies, patient experience, patient opinions and experience, patient perceptions and experience, device acceptability, and patient comfort and concerns were investigated. In four studies, patients were mostly accepting of the wearable devices, reporting positive experiences and satisfaction relating to their use. In three studies, findings were mixed. Conclusion There is limited high‐quality research examining patient acceptability of wearable vital sign monitoring devices as an a priori focus in the acute setting. Further understanding of patient perspectives of these devices is required to inform their continued use and development. Relevance to clinical practice The provision of patient‐centred nursing care is contingent on understanding patients' preferences, including their acceptability of technology use.